A performance comparison between honey and water as electrolytic dielectrics for ZnO liquid-gated transistors - Vieira, Douglas H. [UNESP]; Nogueira, Gabriel L. [UNESP]; Ozório, Maíza S. [UNESP]; Fernandes, José D. [UNESP]; Seidel, Keli F.; Serbena, José P. M.; Alves, Neri [UNESP] (Springer Nature, 2023)
Liquid-gated transistors (LGTs) have attracted considerable attention due to their reduced fabrication time, low cost, and potential use in several applications, such as sensors for in loco diagnosis. Here, we conducted a comparative study of performance between honey-gated (HGT) and water-gated (WGT) transistors, using ZnO as the active layer, highlighting their main electrical characteristics and potential applications. The ZnO/honey and ZnO/water interfaces are attractive for edible and bioelectronics, as both materials are non-toxic and biocompatible. The mobility–capacitance product was determined from the transfer characteristics and found to be μsCi = 2.3 ± 0.8 μF V−1 s−1, and μsCi = 4.3 ± 0.5 μF V−1 s−1 for the WGT and HGT, respectively. Both devices exhibited non-null hysteresis, which was clockwise for the WGT and counterclockwise for the HGT. This phenomenon is linked to the liquid nature of the materials used as an electrolytic dielectric. The viscosity of honey results in lower ion mobility than water, leading to a higher |VTH| shift for the HGT. On the other hand, the WGT presents higher leakage current that dominates the off-state, while in the HGT, it is dominated by the channel resistance, resulting in a high Ion/Ioff ratio of (1.2 ± 0.7) × 104. The remarkable characteristics of the HGTs show that honey has potential as an organic gate dielectric for hybrid devices. With its low leakage current and high Ion/Ioff ratio at low-voltage operation, HGT presents an exciting opportunity as a platform to study material properties.
Keywords: Electrolytic dielectrics; Honey-gated transistor; Liquid-gated transistor; Water-gated transistor